2016
DOI: 10.1515/raon-2015-0015
|View full text |Cite
|
Sign up to set email alerts
|

The impact of anaemia on treatment outcome in patients with squamous cell carcinoma of anal canal and anal margin

Abstract: BackgroundRadiochemotherapy is the main treatment for patients with squamous cell carcinoma of the anal canal. Anaemia is reported to have adverse effect on survival in cancer patients. The aim of the study was to evaluate the influence of anaemia on radiochemotherapy treatment outcome in patients with squamous cell carcinoma of the anal canal.Patients and methodsOne hundred consecutive patients with histologically confirmed squamous cell carcinoma of the anal canal were treated radically with 3-dimensional co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 44 publications
2
16
1
Order By: Relevance
“…Mature outcomes from the ACT-I trial supported evidence for palpable lymphnodes and male sex as prognostic factors for LRR and OS and interestingly, showed that lower baseline hemoglobin levels could predict for the risk of cancer-related death and death from any cause [ 11 ]. It is a common clinical observation that anemia is frequent in cancer patients [ 13 ]. This could substantially increase the proportion of hypoxic cancer cells, leading to an intrinsic resistance to radiotherapy (RT) and chemotherapy (CT), with potential detrimental effects on treatment outcomes [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mature outcomes from the ACT-I trial supported evidence for palpable lymphnodes and male sex as prognostic factors for LRR and OS and interestingly, showed that lower baseline hemoglobin levels could predict for the risk of cancer-related death and death from any cause [ 11 ]. It is a common clinical observation that anemia is frequent in cancer patients [ 13 ]. This could substantially increase the proportion of hypoxic cancer cells, leading to an intrinsic resistance to radiotherapy (RT) and chemotherapy (CT), with potential detrimental effects on treatment outcomes [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…This could substantially increase the proportion of hypoxic cancer cells, leading to an intrinsic resistance to radiotherapy (RT) and chemotherapy (CT), with potential detrimental effects on treatment outcomes [ 14 ]. The impact of hemoglobin level in anal cancer patients submitted to CT-RT has been rarely reported [ 13 , 15 ]. In the present study, we intended to investigate the influence of different clinical prognostic factors, particularly baseline hemoglobin (Hb) levels, on treatment outcomes within a cohort of anal cancer patients submitted to combined RT and CT.…”
Section: Introductionmentioning
confidence: 99%
“…Within the literature, the correlation between prechemoradiotherapy treatment anemia and poor treatment outcome has been widely discussed for other cancers, including lung, breast, cervix, and hematological malignancies [7]. Oblak et al [8] specifically examined the association between patients’ hemoglobin levels prior to commencement of chemoradiotherapy for squamous cell cancer of the anal canal and outcome of treatment. In that study of 100 patients, an hemoglobin >120 g/L was an independent prognostic indicator for survival, in keeping with established literature for other cancers.…”
Section: Discussionmentioning
confidence: 99%
“…For example, preoperative anemia has proved associated with poor prognosis in breast cancer [ 13 ]. The pre-treatment Hb level (cut-off 12 g/dL) was an independent prognostic factor for overall survival in anal canal cancer patients after radiation-chemotherapy [ 35 ]. Pretherapeutic Hb level as an independent useful marker for predicting pathologic tumor response in esophageal squamous cell carcinoma [ 4 ].…”
Section: Discussionmentioning
confidence: 99%